Enhancing utilization of antenatal care services through home-based life-saving skills education among pregnant women in rural Marsabit County, Kenya - Galgalo Halake, Dabo; Rono, Betsy; Gachohi, John M. (International Journal Of Community Medicine And Public Health, 2026)
Background: Low uptake of antenatal care (ANC) contributes significantly to preventable maternal and neonatal deaths, particularly in developing countries. This study evaluated the effectiveness of home-based life-saving skills (HBLSS) education on ANC utilization among pregnant women in rural Marsabit County, Kenya. Methods: A quasi-experimental study was conducted among 256 pregnant women (128 intervention, 128 control). The intervention group received HBLSS education through structured household visits by trained community health promoters, while the control group received standard care. Data were collected at baseline and endline after nine months of the intervention. Key outcomes included ANC uptake, frequency of ANC visits and early initiation of ANC (≤16 weeks of gestation). Chi-square test and Difference-in-Differences analysis were used to determine the intervention effect. Results: ANC utilization at baseline was comparable between groups (p>0.05). At endline, ANC uptake increased significantly in the intervention group (97.6%) compared with the control group (91.7%, p=0.037). Attendance of ≥4 ANC visits increased to 82.9% in the intervention group, while it decreased slightly in the control group (p<0.001). Early initiation of ANC increased to 82.8% in the intervention group versus 57.3% in the control group (p<0.001). Difference-in-Differences analysis indicated a significant positive impact of the intervention across all ANC indicators. Conclusions: HBLSS education delivered at the household level improved ANC utilization, frequency of visits and early initiation of antenatal care services among the pregnant women. Community-based educational interventions can enhance maternal health service uptake in pastoralist and other underserved populations.